Be A Good Listener- Learning from Saint Francis de Sales - Kurnianto, Geovanni Dody (Journal of Asian Orientation in Theology, 2022)
The purpose of the study is to show that the spirituality of Francis de Sales in his work, “Introduction to the Devout Life” is still relevant today, especially for the formation of priests and religious candidates in Indonesia. His work was written when as the Bishop of Geneva, he was concerned for the spiritual life of the laity in his diocese because of the Protestantism movement that swept most of Europe at that time. Francis wants to tell his people that, not only in the Protestant Church, but in the Catholic Church also that holiness belongs to everyone, not only for the clergy, monks, and nuns. His book provides a practical guide for anyone who wants to develop a spiritual life. De Sales offers a new perspective that the first step to develop a spiritual life does not begin with the celebration of the sacraments and liturgies but from the human longing for God that arises from everyone#39;s heart. This longing of God must be cultivated and nurtured, first of all, in spiritual friendship with those who are more experienced in spiritual life. In the formation, this is known in several forms such as spiritual guidance, personal assistance, or cura personalis.